2016
DOI: 10.17795/jjhr-28407
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Prevalence and Genotypes of Torque Teno Virus (TTV) Among Chronic Hepatitis B and C Patients in Ahvaz, 2012

Abstract: Background: Torque teno virus (TTV) belongs to the Circoviridae family and was separated from Japanese patients with elevated levels of serum alanine transferase for the first time. Following this, extensive studies have been carried out around the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…In summary, the highest percentage of TTV infection is among Hepatitis B patients while the lowest is in cardiovascular diseases (CVD) patients. This result is in agreement with other studies which reported more than 70% TTV positivity (Koohi et al, 2012;Hussain et al, 2012b;Magu et al, 2015;Izadi et al, 2016) among hepatitis patients. The low percentage of TTV infection in non-hepatic diseases have been postulated to have an association with less exposure to blood transfusion.…”
Section: 0supporting
confidence: 93%
“…In summary, the highest percentage of TTV infection is among Hepatitis B patients while the lowest is in cardiovascular diseases (CVD) patients. This result is in agreement with other studies which reported more than 70% TTV positivity (Koohi et al, 2012;Hussain et al, 2012b;Magu et al, 2015;Izadi et al, 2016) among hepatitis patients. The low percentage of TTV infection in non-hepatic diseases have been postulated to have an association with less exposure to blood transfusion.…”
Section: 0supporting
confidence: 93%